Study of strength and toughness in pearlitic wheel steel via microstructural alteration - Trivedi R.; Bhumika; Tandon R.; Mishra G.; Singh R.; Singh J.K.; Mahobia G.S.; Chauhan A.; Sarma S.A.R.; Ghosh A.; Karmakar A.; Patra S. (My University, 2025)
The present study investigates a thorough effect of composition, processing, and microstructure on the mechanical property counterpart of pearlitic wheel steel. Optical and scanning electron microscopes along with the ImageJ software are used to capture and quantify the microstructures. Mechanical properties such as hardness, tensile properties, and fracture toughness (K1 C) were measured for all the studied steel. The chemical composition along with the heat treatment parameters are varied in the plant scale processing schedule. It was observed that the volume fraction of ferrite, prior austenite grain (PAG) size and distribution, and pearlite hardness are the most important factors, affecting the strength-toughness combination in the wheel steel. The carbon equivalent and cooling rate are two important factors for the enhancement of tensile strength. The fracture surface investigated under the electron microscope represents the ductile ridges along with the cleavage facets owing to the presence of ferrite allotriomorphs along the PAG and pearlite matrix, respectively. The crack study in the secondary fracture plane shows that the deflection and arrest of cracks were taking place preferentially in the ferrite grain boundaries as well as non-lamellar pearlitic domains. © 2024 Elsevier Ltd